Elastic scattering and inelastic excitation of an unbound state in the fermionic 9Be + 9Be system near the Coulomb barrier - Mayida, Innocent (My University, 2011)
The angular distributions for elastic and, at the highest incident energy, inelastic scattering to the particle-unbound excited state 9Be*(5/2-, 2.430 MeV) in 9Be have been measured in the scattering system 9Be + 9Be at ELab = 9, 12 and 16 MeV. In addition, elastic and inelastic scattering excitation-functions for the 9Be + 9Be system were measured at two different scattering angles (θc.m. = 90° and 50°), over an incident energy range 6 ≤ ELab ≤ 25 MeV. The inelastic scattering cross-sections can be measured by detecting the corresponding recoil nucleus in the scattering process. The experimental work was performed using the 6 MV EN tandem Van de Graaff accelerator at iThemba LABS (Gauteng). The scattered elastic and inelastic 9Be were detected by the ΔE-E gas-ionisation detector and the CAMAC + WIMPS2 data acquisition was used to identify the scattered particles online. Optical model calculations were carried out in order to fit the elastic scattering data and determine an energy-independent optical model potential. Distorted Wave Born Approximation (DWBA) was used to analyse the inelastic scattering with the extracted deformation length, δ2, being in agreement with previous measurements.